Malaysian science and technology indicators - Mohd Asraf, Ratnawati; Alavi, Rokiah; Mohd Amin, Ruzita; Kassim, Salina; Mat Ghani, Gairuzazmi; Hussien, Suhailah (2011)
There is no doubt that S&T plays a pivotal role in the economic and social development of any developed country. Developing countries such as Malaysia have also realized the importance of the role of S&T, and have taken measures to develop their S&T systems. Indeed, not only has Malaysia taken the steps to develop her S&T system, but, like many developed countries before her, has also taken the steps to develop S&T indicators, which are a series of data that are aimed at measuring and reflecting the scientific endeavour of our country, demonstrating the strength and weaknesses of our country’s science system, and providing early warning of events and trends that might impair its ability to meet our country’s needs. Hence, this study on Malaysian S&T indicators was conducted to assess “where we are” with regard to our performance in S&T. Specifically, it sought to determine our standing with regard o education in S&T, human resources in research and development, research and development in S&T public sector support for R&D in science and technology, innovation in the private sector, intellectual property rights, Information and Communications Technology in Malaysia, biotechnology, trade in high technology products, S&T article outputs by Malaysian authors and academics, the public’s awareness in S&T, and recent advancements in the energy sectors. This multi-disciplinary study on the state of S&T in the country has competitiveness, as the results are used in Malaysia’s ranking in indices such as the Global Competitiveness Index, the Innovation Capacity Index, and the World Competitiveness Yearbook Scoreboard.